Effects of Corruption on Educational Administration in a Democratic Nigeria - David Babatunde Akinola; Ogunode N. J. (International Journal on Integrated Education, 2022)
Corruption is a major problem hindering the development of education in Nigeria. Corruption has penetrated the entire educational system. This paper purpose of this paper is to assess the effects of corruption on the educational administration in Nigeria. Data from secondary sources were used to provide empirical backing for the various points raised in the paper. The paper concludes that reduction of funds for school administration, inadequacy of professional teachers, infrastructural facilities, ineffective school supervision, poor staff development, poor achievement of educational objectives, poor quality education, examination malpractices, ineffective educational planning and poor implementation of educational programme are the effects of corruption on the educational administration in Nigeria. In order to address these problems of corruption in the educational administration, the government should fully involve the public in the administration of education in term of funding provision for the sector. Anti-corruption units should be established in all the ministries and agencies of education to help check mate corrupt practices among staff. Regular auditing of commissions, agencies and ministries of education account could help check financial corruption within the system.